(untitled) (Indian Journal of Public Health Research & Development, 2021)
This study is an analysis of five cases of orbital trauma causing proptosis, paralysis of extraocular muscles with or without associated visual failure. All the cases were treated by a ENT and Neurosurgical team. Either a frontal craniotomy or a lateral orbitotomy was performed. Plain X-rays of the skull and Computerised Tomography (C.T. Scanning) were the main investigations. Results were encouraging both functionally and cosmetically. Early diagnosis and an aggressive approach to orbital decompression can achieve good results.